Spatial justice : the basics / Roberto Rocco. - Rocco, Roberto, 1966- (Basics., 2026)
'Spatial Justice: The Basics' offers a concise and accessible introduction to spatial justice as both a theoretical framework and a practical agenda for urban transformation. The book examines how urban space is produced, contested, and governed, and how it is implicated in broader dynamics of inequality, recognition, and participation. Drawing on key thinkers such as Henri Lefebvre, Nancy Fraser, Iris Marion Young, Edward Soja, and Susan Fainstein, the book articulates spatial justice through its distributive, procedural, and recognitional dimensions, while also tracing its intellectual genealogy across critical theory, planning thought, and Southern urbanism.